Analisis Nilai Moral dalam Novel Janji Karya Tere Liye - Faris Al Afif; Ismilatifa Ismilatifa; Annisa Dwi Putri; Salma Srinengsi; Muhammad Rizki (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
This research is motivated by the importance of literary works as a medium for character education that can convey moral values through the experiences of characters and the storyline. The novel Janji by Tere Liye was chosen because it contains various moral values that are relevant to community life and the character formation of students. This study aims to describe the moral values contained in the novel Janji and analyze their relationship within the story structure. The method used is qualitative research with a descriptive approach and content analysis techniques. The main data source is the novel Janji by Tere Liye, while the research data are in the form of excerpts from dialogues, narratives, and events that contain moral values. The results show that the moral values in the novel Janji can be classified into three main relationships, namely the relationship between humans with themselves, with other humans, and with God. The moral values found include honesty, responsibility, hard work, discipline, self-confidence, social awareness, helping each other, respecting others, keeping promises, patience, and religiosity. These values do not stand alone, but are interconnected through character development, conflict, and the storyline. Thus, the novel Janji has strong relevance as a medium for character learning and moral education.